Strengthening Children's Religious Education Impact of the Covid-19 Pandemic Through Family Empowerment - Uksan, Arifuddin (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractThe purpose of this study is to analyze the extent to which the family has an important role in instilling and growing character values that exist in society through strengthening religion in children as a result of the Covid -19 pandemic. The research method used is a qualitative method with a religious approach. Data collection techniques using documentation techniques in the form of scientific journals and books written by competent authors. The study of data analysis used content analysis techniques. The findings of this study are the strategic position of the family, if properly prepared, will become a vital place for human development, especially in preparing human resources who have noble character qualities. On the contrary, it will be a source of disaster when religion in the family is ignored or does not get an adequate portion. This study contradicts the reinforcement theory of motivation proposed by B. F. Skinner but supports the theory of moral strengthening of Imam Al-Gazali. The conclusion of the study is that family empowerment can strengthen the practice of religion in children as a result of the  Covid-19 pandemic which is very strategic because it essentially aims to change individual behavior, knowledge, attitudes and values and skills.AbstrakPenelitian ini bertujuan untuk menganalisis sejauh mana keluarga memiliki peran penting dalam menanamkan dan menumbuhkan nilai-nilai karakter yang ada di masyarakat melalui penguatan agama pada anak akibat pandemi Covid -19. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan religi. Teknik pengumpulan data menggunakan teknik dokumentasi berupa jurnal ilmiah dan buku-buku yang ditulis oleh penulis yang berkompeten. Kajian analisis data menggunakan teknik analisis isi. Temuan penelitian ini adalah posisi strategis keluarga, jika dipersiapkan dengan baik, akan menjadi tempat vital bagi pembangunan manusia, terutama dalam mempersiapkan sumber daya manusia yang memiliki kualitas akhlak mulia. Sebaliknya, akan menjadi sumber malapetaka ketika agama dalam keluarga diabaikan atau tidak mendapat porsi yang memadai. Penelitian ini bertentangan dengan teori penguatan motivasi yang dikemukakan oleh B. F. Skinner tetapi mendukung teori penguatan moral Imam Al-Gazali. Kesimpulan penelitian adalah pemberdayaan keluarga dapat memperkuat pengamalan agama pada anak akibat pandemi Covid-19 yang sangat strategis karena pada hakikatnya bertujuan untuk mengubah perilaku individu, pengetahuan, sikap dan nilai serta keterampilan. How to Cite: Uksan, A. (2021). Strengthening Children's Religious Education Impact of the Covid-19 Pandemic Through Family Empowerment. TARBIYA: Journal of Education in Muslim Society, 8(2), 212-2281. doi:10.15408/tjems.v8i2.25099.